Універсальні вимірювачі RLC на основі уніфікованих апаратно-програмних засобів - Василенко, О.Д.; Мельник, В.Г.; Новік, А.І.; Семеничева, Л.М.; Погребняк, В.Д.; Сліцький, О.В. (Технічна електродинаміка, 2012)
The purpose of this work is substantiation of new approaches to construction of electric measuring devices for wide application. Opportunities of distribution of the signal transformations in measuring channels of devices which are intended for definition of the complex resistance parameters of any kind are considered. The most part of the transforming are carried out by means base hardware - the software complex which is unified for construction of the broad audience of electric systems. Structures of multi-parametric wide-band measuring circuits with use of the integrated components, providing a necessary set of functional transformations of signals and balancing of the bridge for any equivalent circuit of object of measurement are discussed. Mathematical models and algorithms of measuring process are considered.